Vision of the Order, 2002 (Cistercian studies quarterly, 2004)
Focuses on the phenomenon and significance of precariousness. Adaptation of the structures of monastic life to the realities of diminishment; Cistercian life; Incarnation of God's love in the world; Need of a deeper renewal of the charism; Prophetic voices.